The signatures of Anthropocene defaunation: cascading effects of the seed dispersal collapse - Pérez Méndez, Néstor (2016)
Fil: Pérez Méndez, Néstor. Department of Evolutionary Ecology, Estación Biológica de Doñana (EBD-CSIC). Sevilla; España.